2018
DOI: 10.18087/cardio.2018.10.10184
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Heart Disease in Subjects of Young Age: Current State of the Problem: Prevalence and Cardio-Vascular Risk Factors

Abstract: П реждевременной (premature) считают ишемическую болезнь сердца (ИБС), возникшую в возрасте до 55 лет у мужчин и до 65 лет у женщин [1, 2]. Однако в различных исследованиях используется и другая терминология (ИБС в молодом возрасте, ИБС в очень молодом возрасте, преждевременное развитие ИБС), а возрастной предел изучаемых больных варьирует от 35 до 65 лет, что затрудняет сопоставление полученных результатов [3-9]. В последние десятилетия частота развития ИБС у лиц молодого возраста увеличивается, что представл… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
2
0
11
Order By: Relevance
“…[ 28 ] As for FBXO17, previous results showed that FBXO17 expression in tumor tissues of hepatocellular carcinoma (HCC) patients was markedly higher than that in adjacent tissues. [ 29 ] It might promote the malignant progression of HCC by inhibiting the wnt/β-catenin pathway. [ 30 ] In lung adenocarcinoma cells, FBXO17 was observed to promote cell proliferation through activation of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] As for FBXO17, previous results showed that FBXO17 expression in tumor tissues of hepatocellular carcinoma (HCC) patients was markedly higher than that in adjacent tissues. [ 29 ] It might promote the malignant progression of HCC by inhibiting the wnt/β-catenin pathway. [ 30 ] In lung adenocarcinoma cells, FBXO17 was observed to promote cell proliferation through activation of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Ji Wang et al reported that TUBA1C may promote the migration and proliferation of hepatoma cells possibly through the cell cycle signal pathway (26). As for FBXO17, previous results showed that FBXO17 expression in tumor tissues of hepatocellular carcinoma (HCC) patients was markedly higher than that in adjacent tissues (27). It might promote the malignant progression of HCC by inhibiting the wnt/βcatenin pathway (28).…”
Section: Discussionmentioning
confidence: 99%
“…Это обусловлено главным образом ростом распространенности факторов риска (ФР) развития ССЗ. По сравнению с лицами пожилого возраста у больных с ранним дебютом ИБС чаще встречаются такие ФР, как курение, абдоминальное ожирение (АО), отягощенная наследственность, чем такие, как сахарный диабет (СД) и артериальная гипертензия [2][3][4].…”
Section: Introductionunclassified